To a God Unknown play still (Dayton, Ohio)
To a God Unknown play still. This scene shows Joseph Wayne at the base of the sacred rock. This production was directed by Kay Bosse and performed at the Blair Hall Theater, Sinclair Community College, Dayton, Ohio. The actors are unknown.